Protocol for in vivo tracking of lipoproteins in developing oocytes of multiple species of Chagas disease vectors using fluorescent probes - Leonardo L. Fruttero; Jimena Leyria; Pedro A. Paglione; Lilián E. Canavoso (STAR Protocols)
Summary: In insects, the circulating lipoproteins vitellogenin and lipophorin function as yolk protein precursors during oogenesis. Here, we present a protocol for tracing vitellogenin and lipophorin pathways during egg development in three species of Chagas disease vectors (Triatominae, Hemiptera: Reduviidae). We describe steps for purifying and fluorescent labeling of lipoproteins, their injection into vitellogenic females, and analysis using confocal microscopy. This approach enables the fate of lipoprotein particles and their lipid cargo in ovarian tissues to be tracked at the subcellular level.For complete details on the use and execution of this protocol, refer to Fruttero et al.1 and Leyria et al.2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.